Oxidation‐assisted structural elucidation of compounds containing a tertiary amine side chain using liquid chromatography mass spectrometry. (20th April 2018) - Shamai Yamin, Tamar; Prihed, Hagit; Shifrovitch, Avital; Dagan, Shai; Weissberg, Avi
Abstract: A novel analytical technique for the structural elucidation of compounds bearing a tertiary amine side chain via "in vial" instantaneous oxidation and liquid chromatography mass spectrometry (LC‐MS) was developed. A series of lidocaine homologs and benzimidazole derivatives with a major/single amine representative base peak in both their EI‐MS and ESI‐MS/MS spectra were subjected to oxidation by a 0.1% solution of hydrogen peroxide (including several 16 O/ 18 O exchange experiments), followed by LC‐ESI‐MS/MS analysis. The N‐oxide counterparts promoted extensive fragmentation with complete coverage of all parts of the molecule, enabling detailed structural elucidation and unambiguous identification of the unoxidized analytes at low nanogram per milliliter levels.